Clinical application and evaluation of anti-TNF-alpha agents for the treatment of rheumatoid arthritis - Jin Juan; Chang Yan; Wei Wei (Acta Pharmacologica Sinica, 2016)
Rheumatoid arthritis (RA) is a chronic progressive autoimmune disease that dramatically impairs quality of life. A number of compounds are available to treat RA, but they vary in effectiveness. Thus, no optimal treatment strategy has been defined. Currently, disease-modifying anti-rheumatic drugs (DMARDs) and anti-tumor necrosis factor-alpha (anti-TNF-α) agents are considered the treatments of choice. For patients with inadequate responses to DMARD therapy, one recommended therapeutic alternative is anti-TNF-α therapy. Anti-TNF-α agents are effective and have rapid onset of action compared with DMARDs. Elucidating the differences in effectiveness of anti-TNF-α compounds has important clinical implications. By comparing the efficacy, safety and use principle of different treatment options, this review focuses on providing important information about three anti-TNF-α compounds (etanercept, infliximab, and adalimumab) to help define optimal treatments for RA patients.